2003
DOI: 10.1063/1.1591073
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects on the conduction mechanisms of p+-amorphous- Si0.8C0.2:H/n-crystalline-Si diodes

Abstract: P1-type hydrogenated amorphous silicon–carbon (a-Si12xCx :H) on n-type crystalline silicon\ud (c-Si) heterojunction diodes were fabricated and characterized electrically. The effects of thermal\ud annealing on the electrical transport properties of a-Si0.8C0.2 :H/c-Si diodes were investigated by\ud measuring their current–voltage characteristics. From the dark current–voltage characteristics\ud measured at different temperatures (298–373 K), transport mechanisms were analyzed in detail.\ud Two carrier transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…Figure 4displays a plot of parameter A versus temperature. From this plot, the value of parameter A was nearly constant at low temperatures ranging from 200 K down to 50 K. The constant value of parameter A, together with the temperature dependent ideality factor, indicated that the mechanism of carrier transport was governed by a trap-assisted multi-step tunneling process in the hetero junctions [9][10].…”
Section: Figure III a Plot Of Ideality Factor As A Function Of Tempementioning
confidence: 82%
See 1 more Smart Citation
“…Figure 4displays a plot of parameter A versus temperature. From this plot, the value of parameter A was nearly constant at low temperatures ranging from 200 K down to 50 K. The constant value of parameter A, together with the temperature dependent ideality factor, indicated that the mechanism of carrier transport was governed by a trap-assisted multi-step tunneling process in the hetero junctions [9][10].…”
Section: Figure III a Plot Of Ideality Factor As A Function Of Tempementioning
confidence: 82%
“…This implied that the predominant mechanism of carrier transport in the hetero junctions was changed to another mechanism, such as space charge limited current process. Based on this process, the relation between current density and applied bias voltage is written as [10]:…”
Section: Figure IV a Plot Of Parameter A Versus Temperaturementioning
confidence: 99%
“…The parameter X d (nanometer) is given by the expression X d = C W W PC , where W PC (nanometer) is the PDL layer thickness estimated to be 360 nm from our secondary-ion-mass spectroscopy (SIMS) profiles. 9 C W (nondimensional) reflects how steep the boron exponential profile is. In order to reproduce the experimental boron profile.…”
Section: Boron Profile In the Diffused "P…-c-si (Pdl) Layermentioning
confidence: 99%
“…The resulting boron depth profile shows an exponential profile that reaches regions further from the a-c interface at higher temperatures. 9 The doping density in a-SiC is adjusted to match the experimental dark conductivity. The stoichiometry of this film is approximately a-Si 0.8 C 0.2 : H and the dark conductivity is around 32 ⍀ cm −1 .…”
Section: A Modelingmentioning
confidence: 99%
See 1 more Smart Citation